Determinasi Mas?lah?ah Atas Nas?s?; Liberasi Nalar Sharî’ah Najmuddîn al-T?ûfî - Moch. Nurcholis (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
Different from most scholars of Ushul Fiqh, al-T?ûfî tend to put theory mas?lah?ah independence of human reason. For al-T?ûfî vision of a more objective reason in positioning the criteria mas?lah?ah compared to antagonist nas?s? with one another. Therefore, the validity of argument mas?lah?ah should be determinant above the arguments of others, not to mention al-nas?s? al-shar’î though. Pattern of this determination, in analytical with an approach normative-juridical and nature descriptive content analysis. That pattern, departing from the view that to discover the existence of mas?lah?ah not have to wait information and support nas?s?. The mind can independently determine the matters contained therein mas?lah?ah and things are mafsadah. However, in its application, mas?lah?ah must be observed whether related to religious and muqaddarât or related to mu’âmalât and ‘âdat. If related to religious and muqaddarât it must have the support of legality nas?s? and ijmâ’. Unlike the case with regard to issue mu’âmalât and ‘âdat, then mas?lah?ah be the most powerful and independent argument, did not need a legality nas?s? and ijmâ’. In fact, even if turns out mas?lah?ah contrary to nas?s? and ijmâ’, mas?lah?ah must keep favored either with takhs?îs? (specialization) and bayân (explanation) against nas?s? and ijmâ’.